Characterization of Juno in the Film Kucumbu Tubuh Indahku - Ranang Agung Sugihartono; Diego Aiwawi Wanggay (Universitas Padjadjaran, 2023)
Background: The film Kucumbu Tubuh Indahku (Memories of My Body) raises the theme of gender and the social life and culture of the Javanese people. This film has a main character named Juno, who has a strong and interesting character. Purpose: This study aims to explain how the main characters embody the film Kucumbu Tubuh Indahku. The reading of Juno’s character is carried out to explain how the character Juno through his name and appearance, can represent his life as a Lengger dancer. Methods: This research uses a qualitative descriptive approach to explain the characterization using the Telling Method of Albertine Mainderop. Data collection used observation and literature study methods and was processed using qualitative data analysis techniques. Results: This film presents the main character’s complexity from childhood to adulthood. The results of character analysis based on three character dimensions show that physical, sociological, and psychological typologies also influence the determination of character functions. Character development is increasingly obvious when Juno is a small teenager until he grows up. The study shows an overview of Juno’s character and the changes formed by the influence of the sociocultural environment of the community. The character of Juno reflects the conditions of his life journey and the social conditions at that time. Implications: It can provide an overview for society about the psychological life of a man who looks like a woman. It can be a learning tool for novice filmmakers in creating the characters in their films.